WATAK TOKOH, NILAI MORAL, DAN NILAI BUDAYA DALAM NOVEL LOVE SPARKS IN KOREA KARYA ASMA NADIA - ANDRIYANI ANDRIYANI (Universitas PGRI Palembang, 2017)
This study aims to describe the character of the characters, moral values, and cultural values contained in the novel Love Sparks in Korea by Asma Nadia. The method of this research is descriptive qualitative which meant to get figures character, moral values and culture values in Love Sparks in Korea novel by Asma Nadia. Data was collected by library techniques, then recorded in paper based on figures character, moral values and culture values which contained in novel and analyzed. The result of this study are as follows. First, There is thirteen figures character which contained in Love Sparks in Korea novel by Asma Nadia. Second, The strongest moral value which contained in Love Sparks in Korea novel by Asma Nadia is honesty, responsibility, Independently, braverly and modestly. Third, there are culture value which grouped in five relationship patterns, namely: (1) culture value in relationship of human and god; (2) culture value in relationship of human and nature; (3) culture value in relationship fellow human beings; (4) culture value in relationship of human and community; (5) culture value in relationship of human and them self.Keyword : Character, moral values, and cultural values.